Writing for the Ears! - Horo, Ajit (THE PRIMARY TEACHER, 2016)
The conventional way of education, coupled with audio and video resources, can help in understanding and retention of subjects or concepts. The paper, with respect to challenges faced in the education sector, elaborates the impact of adding complementary elements of mass media technology. Further, it categorises the different factors on which learning is dependent.